Remodeling variants and diastolic filling at various stages of diastolic chronic heart failure - I. A. Zavodchikova; T. F. Peretolchina; S. S. Baratz (Российский кардиологический журнал)
Two hundred seven patients with diastolic chronic heart failure (CHF) were examined. Left ventricular (LV) remodeling types were identified in general, and for various functional classes of CHF. Pathophysiology mechanisms of diastolic dysfunction were analyzed. Structural and geometric LV remodeling in CHF was assessed in general and at various CHF stages. Diastolic filling types were analyzed, according to structural and geometric remodeling of left cardiac chambers. Pathogenetic mechanisms of active relaxation disturbance and LV rigidity increase during CHF progression were established.